Prediction of resilient moduli in asphalt mixtures using the Witczak model - Elizondo, Fabián (2025)
This article presents a simplified calculation method of the modulus of bituminous mixtures. This method uses results of basic laboratory tests and general information of materials.  In this investigation an asphalt and ten gradations were analyzed in order to evaluate the Witczak model to predict the modulus of bituminous mixtures and if this could be used with the conditions and characteristics of mixtures in Costa Rica.  The study confirms that the model must be calibrated to the conditions and materials of each country. Finally, the study presents a simplified tool that the engineer can use to predict the modulus in bituminous mixtures and the uses in the structural pavement design.